The Effect of Changing the Contraction Mode During Resistance Training on mTORC1 Signaling and Muscle Protein Synthesis - Ato, Satoru; Tsushima, Daisuke; Isono, Yurie; Suginohara, Takeshi; Maruyama, Yuki; Nakazato, Koichi; Ogasawara, Riki (Frontiers in Physiology, 2019)
Resistance exercise (RE) increases muscle protein synthesis (MPS) via the activation of mechanistic target of rapamycin complex 1 (mTORC1), and resistance training (RT) results in skeletal muscle hypertrophy. Although successive RT induces a blunted MPS response by RE, no effective restorative strategy has been defined. Since eccentric muscle contraction (EC) strongly stimulates mTORC1 activation and MPS, changing the muscle contraction mode to EC might maintain the MPS response to RE during chronic RT. Male rats were randomly divided into RE (1 bout of RE) and RT (13 bouts of RE) groups. Additionally, each group was subdivided into isometric contraction (IC) and EC subgroups. The RE groups performed acute RE using IC or EC. The RT groups performed 12 bouts of RE using IC. The RT-IC subgroup performed a further 13th bout using IC, while the RT-EC subgroup changed to EC for the 13th bout. Muscle samples were obtained at 6 h after exercise in all groups. After the 1st bout of RE, the EC group showed significantly higher p70S6K Thr389 phosphorylation than the IC group. However, the phosphorylation of other mTORC1-associated proteins (4E-BP1 and ribosomal protein S6) and MPS response did not differ between the contraction modes. After the 13th bout of RE, mTORC1 activation and the MPS response were significantly blunted as compared with the 1st bout of RE. Changing from IC to EC did not improve those responses. In conclusion, changing the contraction mode to EC cannot sufficiently reinvigorate the blunted responses of mTORC1 activation and MPS to RE during chronic RT.